Studi Kasus Budaya 6S dalam Penguatan Pendidikan Karakter Peserta Didik Kelas IVA SDN 02 Kota Bengkulu - Amardo, Seftiano; Lusa, Herman; Susanti, Atika (JURIDIKDAS, 2024)
This study aims to find out how the implementation of character education for class IV A students in the application of 6S culture and to determine the inhibiting factors in implementing 6S culture at SDN 02 Bengkulu City. The type of research used is qualitative research with a case study approach. The subjects of the study were school principals, class IVA teachers, and class IV A students who had not implemented a culture that had not implemented 6S culture at SD Negeri 02 Kota Bengkulu. Data collection techniques were observation, interviews, and documentation. Data analysis techniques were the stages of data collection, data reduction, data presentation, and data verification. Data validity techniques were triangulation and member check. The results of this study show that (1) The implementation of student character education in 6S Culture (Smile, Greetings, Greetings, Politeness, Courtesy, Spirit) class IV A at SDN 02 Bengkulu City has not been efficient. The 6S culture at SDN 02 Bengkulu City has two activities, namely routine activities, and activities, to see if the implementation of 6S culture at SDN 02 Bengkulu City is efficient or has not been seen from the stages of cultural habituation Information (Provision of cultural habituation information), Training (cultural habituation training), Modeling (observing cultural habituation), Condition (Conditions of cultural habituation activities), Habituation (Cultural habituation) and Culturalization (Habits that grow) (2) inhibiting factors in the implementation of 6S culture (Smile, Greeting, Greeting, Polite, Polite, Passion) towards the formation of character of grade IV A students at SDN 02 Bengkulu City when viewed from the stages of implementation in cultural implementation, namely Information or information that students can be good or bad, Modelling or models that students exemplify and Conditions or conditions, it can be conditions of residence, home or school.